Digestive hemorrhages: surgical treatment - Praderi, Luis A (Cirugía del Uruguay, 1974)
The subject of digestive hemorrhages demands permant revision for results of therapy still show a high cleathrate. Treatment should be under the can, of a medicosurgical team which should follow evolution, even during periods in Intensive Care Units. Hemorrhages can be divided into two Iarge groups: -High or esophago-duodenal hemorrhages which are generally serious and demand urgency therapy. -Low or pure!y intestina! hemorrhages which are often of minor importance and only demand deferred surgical therapy. Decision as to opportunity for surgery and surgical procedure involve consideration of 4 groups of elements: A) Etiology (frequency and location); B) Pathogeny or bleeding mechanism; C) Intensity and D) Reaction to bleeding according to age, location, etc. Attitude befare hemorrhages should be ec!ectic and not systematic; comparison between conservative and resectionist procedures shows that they are not antagonistic; a careful consideration of clinical situation which should always prevail over paraclínical elements: will indicate which is the most favourable option.